THE INFLUENCE OF ENVIRONMENTAL AWARENESS AND BUSINESS INNOVATION ON THE IMPLEMENTATION OF THE GREEN ECONOMY IN MSMES IN PUYUDAN DUNGDANG VILLAGE - Helwatin Imaniyah; Ubaidullah Muayyad (Jurnal Ikhtibar Nusantara, 2026)
This research focuses on exploring how innovation in business activities and awareness of environmental issues affect the application of green economy principles in MSMEs. This study employs a survey method based on a quantitative approach, with data collected from 100 MSME actors through a questionnaire instrument. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. Findings reveal that environmental awareness has a significant and positive role (p = 0.020) on its own. In addition, business innovation produces a stronger and more dominant effect (p = 0.000). When combined, these two factors significantly shape the adoption of green economy practices. The R² value of 0.859 shows that 85.9% of the changes in green economy implementation are explained by both variables. Promoting sustainability in MSMEs depends on strengthening environmental consciousness alongside continuous innovation in business practices. This study integrates environmental awareness and business innovation into a single model to explain the implementation of the green economy in MSMEs. This study presents a new context in rural MSMEs that has rarely been explored. The findings indicate that business innovation is more dominant than environmental awareness in driving the green economy.